Organizational Communication and Conflict Management - Lani, Ristika; Putri, Rovita Elsa (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
Communication in an organization is an interaction of activity within an organization. But in communication activities may go beyond the boundaries of the organization itself. Often the publications work rather than need to be known to people outside the organization. Become a publication of consumption and become a problem for the organization. Public issues become problematic for that organization. Therefore, the organization of communication problems within the joint organization is important for two things, it's the problem of self-communication and the organization problem. Conflicts within an organization can be avoided but can be eliminated. Conflict within an organization can occur between individuals, a group is an individual conflict between groups and other groups. Not all conflicts have negative and organizational disadvantages. Conflict is capable of making a profit for a well-controlled organization, on the contrary, if the conflict is opened in good control, it could be detrimental to the interests of that organization. All the problems that arise in the organization will soon be solved if it is with the organization and it has taken place within the organization can run healthy.